2011
DOI: 10.1242/dev.058156
|View full text |Cite
|
Sign up to set email alerts
|

Clonal analysis by distinct viral vectors identifies bona fide neural stem cells in the adult zebrafish telencephalon and characterizes their division properties and fate

Abstract: SUMMARYNeurogenesis is widespread in the zebrafish adult brain through the maintenance of active germinal niches. To characterize which progenitor properties correlate with this extensive neurogenic potential, we set up a method that allows progenitor cell transduction and tracing in the adult zebrafish brain using GFP-encoding retro-and lentiviruses. The telencephalic germinal zone of the zebrafish comprises quiescent radial glial progenitors and actively dividing neuroblasts. Making use of the power of clona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
216
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(239 citation statements)
references
References 59 publications
20
216
1
1
Order By: Relevance
“…In agreement, recent imaging and lineage tracing studies in the telencephalon of rodents and zebrafish suggest that the neural stem and progenitor cell pool is gradually exhausted over time and that this may impact neural regeneration (Encinas et al, 2011;Rothenaigner et al, 2011;Barbosa et al, 2015;Calzolari et al, 2015). In the adult zebrafish cerebellum, we detected several-fold activation of VZ progenitors after injury, suggesting that quiescent cells are activated.…”
Section: Exhaustion Of Stem and Progenitor Cells Limits Cerebellar Resupporting
confidence: 89%
“…In agreement, recent imaging and lineage tracing studies in the telencephalon of rodents and zebrafish suggest that the neural stem and progenitor cell pool is gradually exhausted over time and that this may impact neural regeneration (Encinas et al, 2011;Rothenaigner et al, 2011;Barbosa et al, 2015;Calzolari et al, 2015). In the adult zebrafish cerebellum, we detected several-fold activation of VZ progenitors after injury, suggesting that quiescent cells are activated.…”
Section: Exhaustion Of Stem and Progenitor Cells Limits Cerebellar Resupporting
confidence: 89%
“…This is similar to the role of Notch during constitutive neurogenesis in the forebrain of zebrafish (Chapouton et al, 2010;Rothenaigner et al, 2011) and is compatible with a role of Notch signaling in maintaining progenitor pools. Remarkably, the function of Notch in the regenerating spinal cord of zebrafish is similar to its proposed role in the lesioned spinal cord of rats, where Notch is strongly upregulated and acts as an anti-neurogenic factor in vitro (Yamamoto et al, 2001).…”
Section: Discussionsupporting
confidence: 81%
“…In the zebrafish telencephalon, radial glial cells predominantly undergo symmetric gliogenic divisions, which amplify the NSC pool (Rothenaigner et al, 2011). The reason why fish seem to preferentially use this growth mode remains unknown, but it has been shown that a planar orientation of mitoses in neuroepithelia is required for the maintenance of layered structures (Peyre et al, 2011).…”
Section: Discussionmentioning
confidence: 99%